Shared Environment Effects on Children’s Emotion Recognition - Schapira, Rotem; Anger Elfenbein, Hillary; Amichay-Setter, Meirav; Zahn-Waxler, Carolyn; Knafo-Noam, Ariel (Frontiers in Psychiatry, 2019)
Empathy is relevant to many psychiatric conditions. Empathy involves the natural ability to perceive and be sensitive to the emotional states of others. Thus, emotion recognition (ER) abilities are key to understanding empathy. Despite the importance of ER to normal and abnormal social interactions, little is known about how it develops throughout childhood. We examined genetic and environmental influences on children’s ER via facial and vocal cues in 344 7-year- old twin children (59 MZ and 113 same-sex DZ pairs), who were part of the Longitudinal Israeli Study of Twins. ER was assessed with the child version of the Diagnostic Assessment of Nonverbal Accuracy (Nowicki, 2010). For both facial and vocal cues of emotion, twin correlations were not higher for MZ twins than for DZ twins, indicating no heritability for ER in this population. In contrast, correlations were positive for both types of twins (and somewhat higher for DZ twins), indicating a shared environmental effect. This was supported by a bivariate genetic analysis, which did not show a genetic effect but did show shared-environment and non-shared environment effects. This pattern was robust to controlling for twins being of the same sex and age. Effects remained after controlling for background variables such as family income and number of additional siblings. The analysis found a shared environmental correlation between facial and vocal ER (rc =.63), indicating that the shared environmental factors contributed to the overlap between vocal and facial ER. The study highlights the importance of the shared environment to children’s ER.